2018
DOI: 10.1177/0044118x18792437
|View full text |Cite
|
Sign up to set email alerts
|

Experiences Versus Perceptions: Do Students Agree That They Have Been Bullied?

Abstract: Each year, an estimated 30% of school children experience bullying by their classmates. While research has explored the prevalence of bullying, the causes of bullying, and the consequences of bullying, less attention has been focused on understanding how students define bullying experiences. Utilizing a school-based sample of students ranging from fifth to eighth grade, we examine the concordance between the experience of situations defined as “bullying” to the opinions of students as to whether they felt “bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
3
13
1
Order By: Relevance
“…On the whole, this study was the first to validate RBEQ and examine retrospective bullying experiences in Iranian students. The results showed that, meanwhile RBEQ has a single‐factor structure, and only same‐sex bullying occurs in Iranian schools, however, due to the consistency of the findings of the present study with the findings of studies in other cultures regarding normalization of bullying by students (Connell et al, 2019; Parada & Craven, 2002; Runions et al, 2019), high prevalence of reporting bystander role compared to victim or perpetrator roles (Tłuściak‐Deliowska, 2015, 2016), low percentage of reporting bullying perpetration by students (Rivers et al, 2009), high prevalence of bullying incidents in middle school (Rambaran et al, 2020; Salmivalli & Peets, 2018), the stability of different bullying roles over time (Farmer et al, 2011; Tłuściak‐Deliowska, 2015), positive correlation between different bullying roles (Dragone et al, 2020; Walters, 2020), and reliability of RBEQ (Tłuściak‐Deliowska, 2015, 2016), It can be confirmed that RBEQ is a valid and satisfactory questionnaire that can be utilized to determine levels of retrospective bullying experiences of individuals over 18 years of age, in different cultures.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…On the whole, this study was the first to validate RBEQ and examine retrospective bullying experiences in Iranian students. The results showed that, meanwhile RBEQ has a single‐factor structure, and only same‐sex bullying occurs in Iranian schools, however, due to the consistency of the findings of the present study with the findings of studies in other cultures regarding normalization of bullying by students (Connell et al, 2019; Parada & Craven, 2002; Runions et al, 2019), high prevalence of reporting bystander role compared to victim or perpetrator roles (Tłuściak‐Deliowska, 2015, 2016), low percentage of reporting bullying perpetration by students (Rivers et al, 2009), high prevalence of bullying incidents in middle school (Rambaran et al, 2020; Salmivalli & Peets, 2018), the stability of different bullying roles over time (Farmer et al, 2011; Tłuściak‐Deliowska, 2015), positive correlation between different bullying roles (Dragone et al, 2020; Walters, 2020), and reliability of RBEQ (Tłuściak‐Deliowska, 2015, 2016), It can be confirmed that RBEQ is a valid and satisfactory questionnaire that can be utilized to determine levels of retrospective bullying experiences of individuals over 18 years of age, in different cultures.…”
Section: Discussionsupporting
confidence: 77%
“…They recalled their previous bullying‐related experiences and considered bullying incidents a joke. In this regard, evidence has shown that bullies (Parada & Craven, 2002; Runions et al, 2019), bystanders (Parada & Craven, 2002), and victims (Connell et al, 2019; Parada & Craven, 2002) mistakenly believe that school bullying is common phenomena. Indeed, some bullies do not regard their acts as bullying (de Castro et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a similar method used by Connell et al (2019), School Bullying Mismatch captures respondents who report peer victimization using the behavior-specific measure but do not report being the victim of bullying using the generic measure. A categorical variable is created that reflects the type of victimization experienced by the respondent, where 0 = no victimization, 1 = mismatched victimization, and 2 = matched victimization.…”
Section: Methodsmentioning
confidence: 99%